PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA, DAN OCB TERHADAP KINERJA KARYAWAN PT. NARMADA AWET MUDA - Suharja, Rahmat; Agusdin, Agusdin (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This research aims to analyze the Influence of Transformational Leadership, Work Motivation, and Organizational Citizenship Behavior on Employee Performance at PT. Narmada Awet Muda. The type of research used is associative-causal. Data collection method involves a survey by distributing questionnaires to respondents. The data analysis technique used is multiple linear regression with SPSS 21. The sampling method employs proportionate random sampling, resulting in a sample size of 80 individuals from a total population of 399. The analysis results indicate that: Transformational Leadership has a positive and significant effect on employee performance. Work Motivation has a significant influence on employee performance. Organizational Citizenship Behavior does not have a significant effect on employee performance. Transformational Leadership has a positive and significant influence on Organizational Citizenship Behavior. Work Motivation has a positive and significant influence on Organizational Citizenship Behavior. The research recommends that the company provides training to enhance intellectual stimulation for employees, listens to the ideas and suggestions of employees, treats all employees equally, acknowledges and rewards employees for their work, encourages employee participation in organizational meetings, and motivates employees to improve time efficiency in completing tasks.